Why Do Drivers Decide to Violate Traffic Rules while Driving Through Road Tunnels? An Application of the Theory of Planned Behavior - Yan, Guanfeng; Li, Yanjie; Wang, Mingnian; Yan, Tao (KSCE journal of civil engineering, 2024)
Few studies focus on exploring the relationship between psychological factors and drivers’ violation intention in the tunnel sections which feature several adverse characteristics like poor lighting and a monotonous driving environment. In this study, hierarchical multiple regression is adopted to test the predictive effect of the demographic parameters, standard theory of planned behavior (TPB) constructs, and three additional constructs of moral norms, past behavior, and perceived stress to account for intentions to violate traffic rules while driving through road tunnels. In this study, three typical violations while driving inside tunnels including changing the lane, overtaking, and speeding are selected. A sample of drivers (N = 384; 50.3% are men and 49.7% women) were surveyed through a self-report questionnaire. Hierarchical multiple regression analyses show that age appears to be the only significant predictor of violation intention among demographic parameters, and theory of planned behavior (TPB) components account for the majority of the variance in violation intention. In addition, moral norms show a negative significant relationship with violation intention while perceived stress is positively associated with violation intention. The findings could provide an important reference for the development of corresponding interventions.